Emotional involvement and aspirational desire in the journalistic narrative of The Newsroom (HBO). Analysis of the professional audience in Spain - Novoa-Jaso, María Fernanda (2023)
This article presents the results of an investigation carried out on the followers of the television series The Newsroom (HBO) in Spain. Two focus groups (N = 17) were carried out. They included journalists (with different roles in local and national media) and journalism students from various Spanish universities. The participants were questioned about their experiences, knowledge, and perceptions of the plot and the characters of the audiovisual fiction. The interpretation of the data was made from four levels, which evaluated the emotional involvement from lower to higher degree: (1) transportation, (2) identification, (3) parasocial interaction, and (4) worship. The central hypothesis raised the relationship between the ethical values of The Newsroom and the high emotional involvement of the fans. The results obtained will help to understand the high degree of identification of the spectators with the media content. The internalization of ethical values, the adoption of the character's point of view, and the reflection on their informative mission, based on the fiction proposal, are significant aspects. Participants demonstrated an aspirational tendency through empathy and the desire to imitate the main characters. The reasoning of the fans revealed parasocial interactions, and their experiences of transportation (immersion in the story) demonstrated critical skills expressed through counterarguments.